Bilateral conception strategy for efficient design of Lattice models and well Structured Genomic data processing with the semantic web-based system (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Protein folding design and genomic data processing methods are more powerful tools toinvestigate the fundamental principle of IoT based healthcare. In previous researches, proteinfolding has the problem of finding the lowest energy conformation and size complexity. Alongwith this, there is a security problem in genome sequence and complications in storing genomedata due to the unstructured format. To tackle these issues a novel Bilateral conception strategyhas been proposed in this paper. Initially, the problems of finding the lowest energyconformation and size complexity have been solved by a novel Reconcile pirouette mechanismbasedquantum processor through decrease the quantum circuit from quadratic to quasi-linear.Then, the novel Adumbrating algorithm for secure commune based genomic data analysis dealswith the security issue and provides the highest privacy for the genome data by using SingleNucleotide Polymorphisms. Finally, a novel Adroit Semantic web-based system is proposed forsecurely storing and retrieving genome data by Collateral Description frame format. Thus thenovel bilateral conception strategy effectively solves the problem in protein folding and providesa high security and storage format for genome sequence.